PERANCANGAN APLIKASI PENGENALAN ANGGOTA TUBUH MANUSIA DENGAN TIGA BAHASA INDONESIA INGGRIS ARAB BERBASIS ANDROID - Lulu Farhanah; Ardianto Moenir (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The development of information technology has recently grown very rapidly as evidenced by the number of smartphones that have sprung up, one of which is a smartphone with an Android system. Android phones are mobile devices that are becoming a trend in society. The reason is, Android phones have a million features that generally don't exist in the operating system of other cellphones or smartphones. The research method used is the waterfall method including the design of the navigation structure and the design of the display. In making applications made using Android Studio as a Java editor. The design of this application display is divided into 4 main menus, namely: Play, Entertainment, About, and the Exit menu. The Play menu has a Submenu, namely the language selection menu, when we press the language menu in which there are pictures and sounds of pronouncing the names of human body parts in Indonesian, English, and Arabic, while the entertainment options also contain a submenu, namely videos that are viewed and enjoyed by children. This writing has succeeded in making an application design for the introduction of human body parts in three languages ​​​​Indonesian, English and Arabic based on Android and made a compilation with the file name Recognition of human body parts, the size of this application is 189MB. The result of this research is to make an application for Recognizing Human Body Parts in three languages, namely Indonesian, English, Arabic. This research has been tested on several android operations, namely JellyBean, Kitkat and Lollipop.